INFLUENCE OF DIFFERENT CLASSES OF ANTIHYPERTENSIVE DRUGS ON INSULIN RESISTANCE IN PATIENTS WITH MILD AND MODERATE ARTERIAL HYPERTENSION. (June 2018) - Rekovets, O.; Sirenko, Y.; Torbas, O.; Kushnir, S.; Primak, G.; Ponomareva, G.
Abstract : Objective: To reveal the prevalence of metabolic syndrome in patients with hypertension and methods of correction with antihypertensive therapy. Design and method: 223 patients with mild to moderate hypertension (AH) and metabolic syndrome (MS) were screened according to ATP III criteria, of which 105 (47.1%) were males and 118 (52.9%) were females. The average age of patients was 50.29 ± 0.96 years. The average duration of hypertension is 5.01 ± 0.26 years. The average for the office of SBP and DBP was to 157.03 ± 0.79 and 92.17 ± 0.32 mm Hg., heart rate - 75.02 ± 0.69 beats/min. Average daily blood pressure monitoring were 135.90 ± 1.13/80.38 ± 0.81 mm Hg. Patients was devided for groups takes for 6 months atenolol, nebivolol, carvedilol, bisoprolol, fosinopril, telmisartan. Results: Assessing the effect of drugs on the state of insulin resistance, it was found that atenolol, in contrast to fosinopril and telmisartan, significantly impaired IR, which was manifested in an increase in HOMA level by 78.18%, p < 0.05. At the same time, against the background of treatment with fosinopril the HOMA index decreased by 12.5%. However, an even more pronounced improvement in IR was observed in the treatment of telmisartan, HOMA decreased by 31.64%, p < 0.05. The difference between the telmisartan and fosinopril group is significant, p < 0.05. Therapy with carvedilol contributed to a significant decrease in HOMA by 21.7%, p < 0.05. On the background of treatment with bisoprolol, HOMA decreased by 17.4%, p < 0.05, in the group of nebivolol HOMA decreased by 23%, p < 0.05. Thus, telmisartan and nebivolol had the highest positive effect on IR. Conclusions: The use of telmisartan and nebivolol as monotherapy can be rational in patients with mild to moderate arterial hypertension and the clinical signs of a metabolic syndrome without diabetes with manifestations of insulin resistance.